Tracking Cells and Their Lineages Via Labeled Random Finite Sets - Nguyen, Tran Thien Dat; Vo, Ba-Ngu; Vo, Ba Tuong; Kim, Du Yong; Choi, Y.S. (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2021)
Determining the trajectories of cells and their lineages or ancestries in live-cell experiments are fundamental to the understanding of how cells behave and divide. This paper proposes novel online algorithms for jointly tracking and resolving lineages of an unknown and time-varying number of cells from time-lapse video data. Our approach involves modeling the cell ensemble as a labeled random finite set with labels representing cell identities and lineages. A spawning model is developed to take into account cell lineages and changes in cell appearance prior to division. We then derive analytic filters to propagate multi-object distributions that contain information on the current cell ensemble including their lineages. We also develop numerical implementations of the resulting multi-object filters. Experiments using simulation, synthetic cell migration video, and real time-lapse sequence, are presented to demonstrate the capability of the solutions.